Chapter «Li vostri che tenghono li libri non sanno tenere tanti chonnti». Useful knowledge and accounting as seen through the accountant's lenses and the logic of capitalism - Lang, Heinrich (Datini Studies in Economic History, 2023)
Knowledge of accounting before the evolution of academic economic knowledge was practical knowledge. In the context of the studies about the development of accounting techniques, the debates leave out the bookkeeper. The hypothesis here is that, due to the diversification of investments on the behalf of the personal properties in late fifteenth and early sixteenth centuries, an expert accountant appeared as bookkeeper of the personal account books at the merchant bankers' households. In Florence, future merchants were trained in elementary schools and later on in classes the masters of abacus. In their exercise books, the masters of abacus published, we find a lot of algebraic problems which are illustrated by accounting operations. However, at least in Florence manuals on accounting did not exist. So, the young merchant bankers and bookkeepers learned by doing. A case study about an accountant, Matteo Brandolini, who was the bookkeeper of the papal banker's son Alamanno Salviati, shall exemplify this tendency. When the patricians and merchant bankers invested more extensively in secondary markets, they were in the need of highly qualified staff.